Bridging cultures and classrooms: A narrative inquiry into pre-service teachers' international teaching practicum experience - Yuyun, Yuyun; Suhartoyo, Eko; Ubaidillah, M. Faruq; Arepin, Mazlen (UPT Bahasa Universitas Tanjungpura, 2025)
While prior research has widely examined domestic teaching practicum, limited attention has been given to the specific challenges EFL pre-service teachers face in international settings and how these experiences inform their development as educators. Adopting a narrative research design, this study delves into the lived experiences of Indonesian EFL pre-service teachers, uncovering nuanced insights through their stories. The findings reveal four primary challenges: distinguishing academic orders, navigating instructional culture shock, adapting to language barriers, and managing insufficient learning facilities. Despite these hurdles, the PSTs employed innovative coping strategies, transforming obstacles into meaningful learning opportunities. The narrative accounts also highlight five significant benefits gained from the practicum: increased teaching confidence, enhanced skills in lesson planning and activity supervision, alignment of teaching methods with diverse learning styles, improved proficiency in constructing learning assessments, and expanded professional networks. This study encourages teacher education programs to include global teaching competencies and an international teaching curriculum into the teaching and learning enactment.How to cite this paper: Yuyun, Y., Suhartoyo, E., Ubaidillah, M. F., Arepin, M. (2025). Bridging cultures and classrooms: A narrative inquiry into pre-service teachers' international practicum experience. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(1), 123